ROLE OF TAHIR POSHANJI ON BUILDING AN INDEPENDENT ISLAMIC STATE IN AFGHANISTAN (823 – 874 A.D.) - Dadman, Enayatullah; Aminzai, Wafiullah; Dainsh, Mohibullah (American International Journal of Social Science Research, 2021)
This review paper is descriptive in nature and as a time series it investigates role of Tahir Poshanji on building independent Islamic state in Afghanistan. The findings suggest that Tahir Poshanji like other Afghan leaders had a sense of freedom and people of Afghanistan have always made sacrifices for freedom. This caused failure of many great colonial states in their goals. The martyrdom of Abu Muslim caused movements and uprising in Afghanistan which put end to the power of Arab Muslims in Afghanistan. It was in progress until independent Islamic state was built by Tahirid. The war between Mamoon and his brother Ameen over Caliphate provided opportunity to Poshanji and his wish of changing capital of caliphate from Baghdad into Afghanistan. Tahir wanted Afghans to be ruled by people of the Islamic State. The conflicts between Afghans and Arabs were increasing every day. Poshanji started preparation for his map right after his appointment as governor in Afghanistan g to separate Afghanistan from Abbasid Empire. He dropped the caliph’s name from KHUTBA (Islamic Sermon) and proclaimed an independent Islamic state in Afghanistan and raised flag of freedom. His relation with Baghdad Caliphate was only based on respect and not on domination.